ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA DALAM MENYELESAIKAN SOAL FAKTORISASI SUKU ALJABAR BERDASARKAN KESULITAN BELAJAR FAKTOR INTELEKTUAL SISWA PADA KELAS VIII B SMP N 8 SURAKARTA TAHUN AJARAN 2016/2017 - Novita Ayu Dewanti; Ponco Sujatmiko; Getut Pramesti (Phenomenon : Jurnal Pendidikan MIPA, 2018)
This study aims to describe the understanding of students' mathematical concepts in solving the factorization of algebraic tribes. The method used is descriptive qualitative. The subjects of the study were 6 students of class VIII B Surakarta State Junior High School 8 divided into 3 groups, namely the group of low, medium and high learning difficulties. Data collection techniques include tests and interviews. The results showed that (1) students who had low learning difficulties were able to master most of the indicators that were determined, only one indicator that had not been mastered, namely determining variables. (2) Students who have moderate learning difficulties have been able to master most of the indicators set, but there are indicators that have not been mastered, namely determining variables and there are several indicators that have not been smoothly mastered. (3) Students who have high learning difficulties have been able to master to determine examples of algebraic problems and students have not been able to master the indicators stating an operation, completing various algebraic forms, operating and using them.